Relationship Between Maternal Economic Vulnerability and Childhood Neurodevelopment at 2 and 5 Years of Life. Issue 3 (September 2021) - Premkumar, Ashish; Mele, Lisa; Casey, Brian M.; Varner, Michael W.; Sorokin, Yoram; Wapner, Ronald J.; Thorp, John M.; Saade, George R.; Tita, Alan T.N.; Rouse, Dwight J.; Sibai, Baha; Costantine, Maged M.; et al.
Abstract : OBJECTIVE: To assess the relationship between economic vulnerability during pregnancy and childhood neurodevelopment. METHODS: This is a secondary analysis of two parallel multicenter, randomized, controlled trials of administration of levothyroxine to pregnant individuals with subclinical hypothyroidism or hypothyroxinemia in the United States. All participants who delivered a live, nonanomalous neonate and completed the WPPSI-III (Weschler Preschool & Primary Scale of Intelligence) at 5 years of life and the Bayley-III (Bayley Scales of Infant Development) test at 2 years were included. The primary outcome is WPPSI-III score. Secondary outcome included Bayley-III subtest scores. Multivariable analyses were used to assess the relationships between economic vulnerability during the index pregnancy —defined as a household income less than 200% of the estimated federal poverty level, part-time or no employment, and use of government insurance—and the prespecified outcomes. Tests of interaction were performed to assess whether the magnitude of association differed according to whether participants were married or completed more than a high school education. A sensitivity analysis was performed to limit the income criteria for economic vulnerability to household income of less than 100% of the estimated federal poverty level. RESULTS: Of 955 participants who met inclusion criteria, 406 (42.5%) were considered economically vulnerable. In bivariate analysis, the WPPSI-III score and Bayley-III subtest scores were significantly lower among children of the economically vulnerable. For the WPPSI-III, Bayley-III cognitive subtest, and Bayley-III language subtest scores, the associations between economic vulnerability and lower childhood neurodevelopmental scores were primarily seen only among those who were married or completed more than a high school education ( P for interaction<.05). A similar pattern was noted when restricting the income criteria for economic vulnerability to less than 100% of the federal poverty level. CONCLUSION: Economic vulnerability during pregnancy is associated with an increased risk of adverse neurodevelopmental outcomes in their children at 2 and 5 years of life, particularly among those who are married or completed more than a high school education. Abstract : Exposure to economic vulnerability during pregnancy is associated with increased risk of adverse childhood neurodevelopmental outcomes, particularly among participants who were married or had more education.